Impact of supramolecular interactions of dextran-β-cyclodextrin polymers on invertase activity in freeze-dried systems - Santagapita, Patricio Roman (2015)
β-cyclodextrin-grafted dextrans with spacer arms of different length were employed to evaluate the impact of supramolecular interactions on invertase activity. The modified dextrans were used as single additives or combined with trehalose in freeze-dried formulations containing invertase. Enzyme activity conservation was analyzed after freeze-drying and thermal treatment. The change of glass transition temperatures (Tg) was also evaluated and related to effective interactions. Outstanding differences on enzyme stability were mainly related to the effect of the spacer arm length on polymer-enzyme interactions, since both the degree of substitution and the molecular weight were similar for the two polymers. This change of effective interactions was also manifested in the pronounced reduction of Tg values, and were related to the chemical modification of the backbone during oxidation, and to the attachment of the β-cyclodextrin units with spacer arms of different length on dextran.